Surgical treatment of extended spongy urethral strictures in men: minimizing the risks of narrowing in the anastomotic zones between the buccal graft and the native urethra using the dorsal inlay technique - V. V. Mitusov; M. I. Kogan; Z. A. Mirzaev; V. P. Glukhov; B. G. Amirbekov (Вестник урологии, 2021)
Introduction. Currently, the most common method of treating extended urethral strictures is augmentation urethroplasty using oral mucosa grafts. Analysis of the long-term outcomes of this surgery type shows a high incidence of relapses and complications.Purpose of the study. To improve the outcomes of augmentation urethroplasty, in particular the dorsal inlay (Asopa) technique, in patients with extended spongy urethral strictures by minimizing the risk of recurrent strictures.Materials and methods. The study is based on an analysis of the surgery in 90 patients (aged 18-72 years) with extended spongy urethral strictures. Seventy patients (group I) underwent dorsal inlay augmentation urethroplasty according to the Asopa technique, and 20 patients (group II) — according to the author's modified technique. Statistical data analysis was carried out using the SPSS ver.26 software (SPSS Inc. Chicago, IL, USA).Results. A comparative analysis of the course of the early postoperative period showed a lower number of complications in group II patients compared to group I — 20.0% versus 34.3%, respectively. The recurrent strictures were registered for groups I and II in 18.8% and 5.6% of cases 6 months after surgery, respectively. The recurrent urethral narrowing was most often localized in the area of distal anastomosis between the buccal graft and the native urethra in patients from both groups.Conclusion. The modified dorsal inlay augmentation urethroplasty technique developed and implemented in clinical practice by increasing the internal urethral lumen in the areas of proximal and distal anastomosis between the buccal graft and the native spongy urethral body allows minimizing the risks of recurrent urethral narrowing after augmentation urethroplasty.